GLOCALIZATION IN FOOD NAMING IN CENTRAL AND EAST JAVA: THE STUDY OF THE WORD ETYMOLOGY - Adista Nur Primantari; Elita Ulfiana (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
The glocalization of foreign cultures in Indonesia includes one of them is in the culinary field. From different regions the names of foods originating from foreign countries are modified based on the ease of pronunciation, shape, type and texture of the food. The purpose of this study is to analyze and uncover by analyzing culinary names in Central Java and East Java that have etymology. This type of research is literature, namely by using literature from the Kamus Besar Bahasa Indonesia (KBBI) Daring V and Oxford English Dictionary (OED). Based on the results of the study, culinary names in Central Java and East Java have differences from the origin of words, the use of spices, cooking methods and taste preferences of people in the two provinces.